Depression, anxiety and stress among diabetic and non-diabetic patients with periodontitis - Faisal, Ghasak Ghazi; Al-Ani, Ali Sabri Radeef (Ektodermal Displazi Grubu, 2017)
The aim of this study is to determine the prevalence and severity of depression, anxiety and stress among diabetic patients with periodontitis and to assess the association of emotional disturbances with the severity of periodontitis. A total of 72 diabetic patients with periodontitis and 87 non diabetic patients with periodontitis who attended Kulliyyah of Dentistry periodontics clinic, International Islamic University Malaysia were randomly selected. The patients underwent a full-mouth clinical examination by a periodontics specialist. The prevalence and severity of depressive, anxiety and stress symptoms (DAS) were assessed among those patients by using the self-rating Malay version of the Depression Anxiety and Stress Scale (DASS-21). Diabetic patients had higher rates of depression 27.7%, anxiety 50% and stress 34.8% compared to the non-diabetic group rate of 11.4%, 25.3% and 6.8% respectively. More diabetic patients showed clinically significant DAS than the non-diabetic group indicating more severe emotional disturbances. The mean scores of DAS among the diabetic group were significantly higher (p<0.05) than non-diabetics. The mean scores of DAS were also higher among patients with advanced periodontitis than mild periodontitis. Emotional disturbances are occurring in a high rate in diabetic patients with periodontitis which can affect the severity of the periodontitis. Managing diabetic patients need to be more comprehensive by focusing on the psychological as well as the physical wellbeing of the patients leading to more efficient treatment of diabetes and its complications